2018
DOI: 10.17265/2162-5298/2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development of the City’s Transport Infrastructure—A Project of a New Tram Line with a Linear Park along the Exhibition Channel in Warsaw

Abstract: A new double-circuit tram route planned in Warsaw (V max = 70.0 km/h), running through the Praga Południe district from Waszyngton Avenue (Washington Avenue) to Gocław loop (total length of about 3.5 km), is designed to reduce the existing road load in this area of the access routes from outside Warsaw to the center of the capital, as well as to improve the conditions of transport service in the areas of Saska Kępa, Międzynarodowa housing estate, Kępa Gocławska and Gocław, thereby increasing the use of public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In this case, the greenery is also a recreational space, besides having the isolating function. Such solutions are popular around the world [1][2][3][4][5][6]9,[67][68][69][70][71][72][73], and this trend is also provided for in the design of the environment of tram route Saska Kępa-Gocław, in which the authors participated [10]. Furthermore, the conceptual research concerning the greenery structure accompanying the tram lines has shown great socioeconomic importance of the public consultations at the stage of the project preparation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case, the greenery is also a recreational space, besides having the isolating function. Such solutions are popular around the world [1][2][3][4][5][6]9,[67][68][69][70][71][72][73], and this trend is also provided for in the design of the environment of tram route Saska Kępa-Gocław, in which the authors participated [10]. Furthermore, the conceptual research concerning the greenery structure accompanying the tram lines has shown great socioeconomic importance of the public consultations at the stage of the project preparation.…”
Section: Discussionmentioning
confidence: 99%
“…The presented case studies of cities show that a complex, coherent, and thoughtful approach to tramway lane design results in their successful integration with the urban surroundings [2,3,5,9,10,67]. The current world standard trams are environmentally friendly; they move almost noiselessly-often on surfaces covered with vegetation or in "green corridors"-without degrading visually valuable, often historic downtown areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations